1999
DOI: 10.1046/j.1365-2796.1999.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and clinical significance of thrombocytosis: analysis of 732 patients with an elevated platelet count

Abstract: Abstract. Griesshammer M, Bangerter M, Sauer T, Wennauer R, Bergmann L, Heimpel H (University of Ulm, Germany). Aetiology and clinical significance of thrombocytosis: analysis of 732 patients with an elevated platelet count. J Intern Med 1999; 245: 295±300.Objective. To determine the aetiology and clinical significance of an elevated platelet count (thrombocytosis) in a large cohort of patients. Design. A retrospective review of the medical records was performed on all patients, who had at least one platelet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
171
4
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(195 citation statements)
references
References 23 publications
13
171
4
7
Order By: Relevance
“…A recent study investigating etiology and clinical significance of thrombocytosis found a higher incidence of venous and arterial thrombosis in patients with primary thrombocytosis as compared to patients with secondary thrombocytosis (12.4% vs. 1.6%). The authors conclude that postsplenectomy thrombocytosis is not associated with an increased risk for hemostatic complications [20]. Thus thrombocytosis by itself does not seem an indication to initiate anti-coagulation or antiplatelet or plateletlowering therapy unless it is being used as secondary prophylaxis.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study investigating etiology and clinical significance of thrombocytosis found a higher incidence of venous and arterial thrombosis in patients with primary thrombocytosis as compared to patients with secondary thrombocytosis (12.4% vs. 1.6%). The authors conclude that postsplenectomy thrombocytosis is not associated with an increased risk for hemostatic complications [20]. Thus thrombocytosis by itself does not seem an indication to initiate anti-coagulation or antiplatelet or plateletlowering therapy unless it is being used as secondary prophylaxis.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, under some circumstances, regulation of hepatic production may also be a mechanism for controlling TPO levels. Thrombocytosis in humans is observed in hospitalized patients with infection, cancer, and chronic inflammation (21,22), and this is frequently associated with increased circulating TPO (23). The liver mediates many of the protein changes recognized during the acutephase response, and pathways present in the liver that produce reactive changes in TPO may provide a mechanistic explanation for these clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…Although TPO production does not appear to be altered in the liver in response to alterations in platelet counts, it is less certain whether altered production of the hormone is responsible for the thrombocytosis seen in in¯ammatory conditions. It is clear that platelet counts rise in response to in¯ammation (Griesshammer et al, 1999), and with the development of reliable immunoassays of TPO, 50 ± 500% increases in blood TPO concentrations have been found in thrombocytotic post-surgical patients and in individuals with Crohn's disease and other in¯ammatory conditions (Cerutti et al, 1997;Uppenkamp et al, 1998;. Thus, the regulation of TPO production and levels may be rather complex.…”
Section: The Regulation Of Thrombopoietin Levelsmentioning
confidence: 99%